Assessing researchers' capabilities, opportunities, and motivation to conduct equity-oriented dissemination and implementation research, an exploratory cross-sectional study - Ana A. Baumann; Eva N. Woodward; Rajinder Sonia Singh; Prajakta Adsul; Rachel C. Shelton (BMC, 2022)
Abstract Background A recent paradigm shift has led to an explicit focus on enhancing health equity through equity-oriented dissemination and implementation (D&I) research. However, the integration and bidirectional learning across these two fields is still in its infancy and siloed. This exploratory study aimed to examine participants' perceived capabilities, opportunities, and motivations to conduct equity-oriented D&I research. Methods We conducted an exploratory cross-sectional survey distributed online from December 2020 to April 2021. Participants were recruited at either D&I or health disparities-oriented conferences, meetings, through social media, or personal outreach via emails. Informed by the Capability, Opportunity, and Motivation Model (COM-B), the survey queried respondents about different aspects of engaging in and conducting equity-oriented D&I research. All analyses were conducted in SPSS Version 27.0. Results A total of 180 participants responded to the survey. Most participants were women (81.7%), white (66.1%), academics (78.9%), and faculty members (53.9%). Many reported they were advanced (36.7%) or advanced beginners (27.8%) in the D&I field, and a substantial proportion (37.8%) reported being novice in D&I research that focused on health equity. Participants reported high motivation (e.g., 62.8% were motivated to apply theories, models, frameworks for promoting health equity in D&I research), but low capability to conduct equity-oriented D&I research (e.g., 5% had the information needed for promoting health equity in D&I research). Most participants (62.2%) reported not having used measures to examine equity in their D&I projects, and for those who did use measures, they mainly used individual-level measures (vs. organizational- or structural-level measures). When asked about factors that could influence their ability to conduct equity-oriented D&I research, 44.4% reported not having the skills necessary, and 32.2% stated difficulties in receiving funding for equity-oriented D&I research. Conclusions Study findings provide empirical insight into the perspectives of researchers from different backgrounds on what is needed to conduct equity-oriented D&I research. These data suggest the need for a multi-pronged approach to enhance the capability and opportunities for conducting equity-oriented D&I work, such as: training specifically in equity-oriented D&I, collaboration between D&I researchers with individuals with expertise and lived experience with health equity research, funding for equity-oriented D&I research, and recognition of the value of community engaged research in promotion packages.